Working on the Margins: Comparative Perspectives on the Roles and Motivations of Peripheral Actors in Journalism - Schapals, Aljosha Karim (2019)
As a consequence of digitization and other environmental trends, journalism is changing its forms and arguably also its functions—both in fundamental ways. While ‘legacy’ news media continue to be easily distinguishable by set characteristics, new content providers operating in an increasingly dense, chaotic, interactive, and participatory information environment still remain somewhat understudied. However, at a time when non-traditional formats account for an ever-growing portion of journalistic or para-journalistic work, there is an urgent need to better understand these new peripheral actors and the ways they may be transforming the journalistic field. While journalism scholarship has begun to examine peripheral actors’ motivations and conceptualizations of their roles, our understanding is still fairly limited. This relates particularly to comparative studies of peripheral actors, of which there have been very few, despite peripheral journalism being a global phenomenon. This study aims to address this gap by presenting evidence from 18 in-depth interviews with journalists in Australia, Germany, and the UK. In particular, it examines how novel journalistic actors working for a range of organisations discursively contrast their work from that of others. The findings indicate that journalists’ motivations to engage in journalism in spite of the rise of precarious labour were profoundly altruistic: Indeed, journalists pledged allegiance to an ideology of journalism still rooted in a pre-crisis era—one which sees journalism as serving a public good by providing an interpretative, sense-making role.